Associations of body mass index with severe outcomes of COVID-19 among critically ill elderly patients: A prospective study - Gholi, Zahra; Vahdat Shariatpanahi, Zahra; Yadegarynia, Davood; Eini-Zinab, Hassan (Frontiers in Nutrition, 2023)
ABSTRACT Background and aim: Few studies assessed the associations of overweight and obesity with severe outcomes of coronavirus disease 2019 (COVID-19) among elderly patients. This study was conducted to assess overweight and obesity in relation to risk of mortality, delirium, invasive mechanical ventilation (IMV) requirement during treatment, re-hospitalization, and prolonged hospitalization and ICU admission among elderly COVID-19 patients. Methods: This was a single center prospective study that was done on 310 elderly COVID-19 patients hospitalized in the intensive care unit (ICU). We collected data on demographic characteristics, laboratory parameters, nutritional status, blood pressure, comorbidities, medications, and types of mechanical ventilation at baseline. Patients were followed up during ICU admission and until 45 days after the first visit and data on delirium incidence, mortality, need to a form of mechanical ventilation, discharge day from ICU and hospital, and re-hospitalization were recorded for each patient. Results: During the follow-up period, we recorded 190 deaths, 217 cases of delirium, and 35 patients that required IMV during treatment. After controlling for potential confounders, a significant association was found between obesity and delirium; such that, obese COVID-19 patients had a 62% higher risk of delirium compared with the normal-weight patients (HR: 1.62, 95% CI: 1.02-2.57). This association was not observed for overweight. In terms of other outcomes including ICU/45-day mortality, IMV therapy during treatment, re-hospitalization, prolonged hospitalization, and ICU admission, we found no significant association with overweight and obesity either before or after controlling for potential confounders. Conclusion: We found that obesity may be a risk factor for delirium among elderly critically ill COVID-19 patients.